Comparison of Analgesic E?ect of Intrathecal Fentanyl & Dexmedetomidine with Hyperbaric Bupivacaine in Orthopedic Lower Limb Surgery - Usha P. Patel; Pravinkumar Chunilal Patel (Academia Anesthesiologica International, 2021)
Background: To evaluate effectiveness of dexmedetomidine and fentanyl supplementary to intrathecal bupivacaine in orthopedic events in lower limbs at stipulations of block potency and instance. Subjects and Methods: in the present study, 120 subjects enduring possible lower limb surgeries were arbitrarily owed to bupivacaine and normal saline (BN), bupivacaine and dexmedetomidine (BD) and bupivacaine and fentanyl. Hemodynamic changes, the maximum sensory level, regression from block, analgesic request, Time to attain the whole motor block, and period of the drug consequence, and side effects were evaluated among the groups. Results: There was noteworthy dissimilarity among BD with BF and BN groups in terms of all parameters like two segmental regression, regression to Bromage etc. Conclusion: Dexmedetomidine as a subsidiary to bupivacaine for intrathecal analgesia in lower limb surgeries has larger period of sensory and motor block, larger postoperative analgesia with little consequences.